Fish Consumption Habits and Diversity of Fish Species in Front the Second Dam of Nam Ou, Luangprabang Province - Kulamany, Sanaphay; Onphachanh , Xaykham; BRIATIA, Xoxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study aims to observe of fish consumption habits and diversity of fish species in front of Nam Ou Dam 2. The study procedure was did by using interview form (Log book model) for interview the farmer sampling groups with 245 households from 4 villages during August, 2020 to March, 2021 for the data of fish consumption habits. Fish diversity survey was done according to the sampling of fish catched from each pointed (10 points) of each time in front of Nam Ou Dam 2. Results found that all most of people living in front of Nam Ou Dam 2 were 97.14% farmers, 2.04% government staffs and 0.82% business or trader. Fish consumption habits found more than 40% were raw or uncooked, 35.10% medium cooked and 24.90% cooked. The frequency consumption fish was approximately 9 times and/or more than 9 times a week, and the frequency of catched fish were 38-81 times/month with amount of fish 51-76 kg/time. The main sources of fish for consumption were catched by famers or fishers 96.61% and about 9.39% was brought from the local market. Diversity of fish found during the August, 2020 to March, 2021 were 8 Oders, 17 Families, and 39 Species. However, Oder of Cypriniformes was found with 2 families and 21 species, Oder of Siluriformes found with 5 families and 7 species, and Oder of Perciformes found with 5 families and 6 species. Whereas, Oder of Clupeiformes, Osteoglossiformes, Synbranchiformes, Pleuronectiformes and Tetraodontiformes were found with each of only 1 families and 1 species, respectively.